Foreign Trade of Iraq Between the imperatives of economic diversification And the challenges of joining the (WTO) - معله, حالوب كاظم; سلمان, مروة خضير (Journal of Economics and Administrative Sciences, 2016)
Interested in this research shed light on the reality of foreign trade to Iraq Who suffers from a marked deterioration due to poor economic diversification of the country And increase the degree of economic exposure   , Which creates a state of extreme caution towards the question of accession to the (WTO)   , As controls Iraq's foreign trade commodity  , a president of one oil As well as the contribution of this item  , and by a large formation in GDP   , And that such a large and dangerous decline in the degree of economic diversification will create negative effects On overall economic activity components   , As the scarcity of commodity products will inevitably lead To weakness in the domestic market's ability to meet the domestic demand  , Which will open the door to imports of goods to invade this market   , Supported in financing the movement of such imports Are being provided by oil exports of financial revenues As a result of that process will be generated negative impact on the trade balance of the country And the value of local currency As well as direct effects on cash reserves of hard currency held by Country   , These structural imbalances in Iraq's foreign trade requires On the Iraqi economy and the current wait own reality on the subject of accession to the World Organization   , Because joining lead to damage in the economic activity in the physical potential Because of the lack of a local product  , whether industrial or agricultural competitor for foreign products   , Which will lead to a lack of hope in the revival of the domestic industry and the advancement of the agricultural sector   , The potential industrial and agricultural sector is not commensurate with their counterparts in the economies of the countries Members of the acceding which will not qualify for entry in the successful competition with the products of these countries   , And also lead to join the organization continued exposure economy with a high degree on the outside and a lot of other negatives and the damage that will cause the Iraqi economy .